IMPLEMENTASI PROFIL PELAJAR PANCASILA PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV DI SD NEGERI BENDUNGAN SEMARANG - Setiyaningsih, Linda; Listyarini, Ikha; Wati, Lolok Eko; Artharina, Filia Prima (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
Education is a very important part in the process of developing the character of a nation. Quality education can influence human resources to be ready to face competition in society as a form of good learning experience and education is interpreted as a very important factor in life. Character development can be carried out in Pancasila education learning through the Pancasila student profile contained in the Merdeka curriculum so that it can improve good character for students. The type of research used is qualitative description. The methods used are observation, interviews and documentation. The data analysis method used is triangulation. Based on the data, it was found that the training carried out was in accordance with the six characteristics of the Pancasila student profile, namely faith, devotion to God Almighty and noble character, global diversity, mutual cooperation, independence, critical reasoning and creativity.Â